Heavy oil recovery and upgrading - Speight, James G. (Elsevier, 2019)
'Heavy Oil Recovery and Upgrading' covers properties, factors, methods and all current and upcoming processes, giving engineers, new and experienced, the full spectrum of recovery choices, including SAGD, horizontal well technology, and hybrid approaches. Moving on to the upgrading and refining of the product, the book also includes information on in situ upgrading, refining options, and hydrogen production. Rounding out with environmental effects, management methods on refinery waste, and the possible future configurations within the refinery, this book provides engineers with a single source to make decisions and manage the full range of challenges. -- Provided by publisher.
Keywords: Heavy oil.; Oil well drilling.; Petroleum -- Refining.; elektronické knihy; electronic books